Life, liberty, and the pursuit of Dao : ancient Chinese thought in modern American life - Crane, George T., 1957- (Blackwell public philosophy, 2013)
This highly original work introduces the ideas and arguments of the ancient Chinese philosophies of Confucianism and Daoism to some of the most intractable social issues of modern American life, including abortion, gay marriage, and assisted suicide. Introduces the precepts of ancient Chinese philosophers to issues they could not have anticipatedRelates Daoist and Confucian ideas to problems across the arc of modern human life, from birth to deathProvides general readers with a fascinating introduction to Chinese philosophy, and its continued relevance.